A case report of autoimmune pancreatitis associated with a pancreatic pseudocyst. Issue 19 (May 2018) - Zhang, Kai; Liu, Xianying; Yi, Lei; Li, Jiannan; Shi, Jian; Liu, Tongjun
Abstract: Rationale: Autoimmune pancreatitis (AIP) is a special type of chronic pancreatitis, which is rarely associated with pseudocyst. Patient concerns: A 48-year-old man complained of a recurrent upper abdominal pain in our hospital. Diagnoses: A cystic mass of size 4 × 3 cm in his pancreatic tail was found by computed tomography. The concentrations of serum carbohydrate antigen19–9 (81 U/mL) and serum immunoglobulin G4 (181 mg/dL) were elevated. Interventions: The patient received partial pancreatectomy with splenectomy and partial esophagectomy. Outcomes: Further histopathological examination revealed a pseudocyst, significant lymphoplasmatic infiltration, and fibrosis in the pancreas and esophagus. We report a rare case of AIP complicated with a pancreatic pseudocyst and invasion of lower esophagus. Lessons: Our study demonstrated that surgical therapy should be considered for the refractory AIP complicated with a pancreatic pseudocyst and invasion of lower esophagus.